PERAN PENYULUH AGAMA DALAM MENCEGAH KONFLIK KELUARGA MELALUI METODE BIMBINGAN KONSELING ISLAM - Suryadi Suryadi; Imam Turmudi; Hosnul Abrori (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
A religious instructor is someone who has the goal of enlightening and enlightening the community who acts as a deterrent, companion, and as a mediator for the community in Jatibanteng sub-district. Religious instructors themselves are education that provides religious enlightenment to people who are not limited by space and time, especially in terms of preventing family conflicts. Efforts to prevent and handle family conflicts are very much needed in the community from before marriage (pre-marriage). The focus of the problems in this study are: 1) What is the role of religious instructors in preventing family conflicts in KUA, Jatibanteng District, Situbondo Regency? 2) What are the methods of Islamic counseling guidance used in preventing family conflicts in KUA, Jatibanteng sub-district, Situbondo Regency? The purposes of this study are, 1) to determine the role of religious instructors in preventing family conflicts in KUA, Jatibanteng District, Situbondo Regency. 2) To find out the method of Islamic counseling guidance used in preventing family conflicts in the KUA, Jatibanteng sub-district, Situbondo Regency. The type of research in this study is field research. Data collection techniques used are observation, structured interviews, and documentation. The data analysis used is a qualitative analysis with a deductive method. The researcher tested the validity of the data by using source triangulation. This study concludes that 1) the role of religious instructors in preventing family conflicts in KUA Jatibanteng District is as a deterrent, companion and as a mediator. 2) Islamic counseling guidance methods used by religious instructors are premarital counseling and family counseling.